2019
DOI: 10.3847/1538-4357/ab2238
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Mg ii h, k and Triplet Lines at Solar Flare Ribbons

Abstract: Observations from the Interface Region Imaging Spectrograph (IRIS) often reveal significantly broadened and non-reversed profiles of the Mg II h, k and triplet lines at flare ribbons. To understand the formation of these optically thick Mg II lines, we perform plane parallel radiative hydrodynamics modeling with the RADYN code, and then recalculate the Mg II line profiles from RADYN atmosphere snapshots using the radiative transfer code RH. We find that the current RH code significantly underestimates the Mg I… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 59 publications
3
41
1
Order By: Relevance
“…In addition to previous studies (Rubio da Costa and , recent work by Zhu et al (2019) has succeeded in reproducing some of these profiles assuming very large electron energy fluxes (typical of a X-class flare) and increased Stark widths. Nevertheless, it is still unclear how to reproduce such single-peaked profiles in the case of smaller flares, and how to fully explain their increased broadening.…”
Section: Iris Lines As Diagnostics Of Flare Heating Mechanismsmentioning
confidence: 63%
See 2 more Smart Citations
“…In addition to previous studies (Rubio da Costa and , recent work by Zhu et al (2019) has succeeded in reproducing some of these profiles assuming very large electron energy fluxes (typical of a X-class flare) and increased Stark widths. Nevertheless, it is still unclear how to reproduce such single-peaked profiles in the case of smaller flares, and how to fully explain their increased broadening.…”
Section: Iris Lines As Diagnostics Of Flare Heating Mechanismsmentioning
confidence: 63%
“…Puzzling blue-wing enhancements in the Mg II lines (Tei et al, 2018;Huang et al, 2019a) have also been observed and could be indicative of "cool upflows", caused by non-thermal electrons penetrating much deeper into the lower atmosphere than expected and causing an upward motion in the upper chromosphere (Huang et al, 2019a;Zhu et al, 2019;Hong et al, 2020). A recent study has also shown that the location where the cool upflows occur varies in different flare models (Hong et al, 2020).…”
Section: Iris Lines As Diagnostics Of Flare Heating Mechanismsmentioning
confidence: 90%
See 1 more Smart Citation
“…If we increase the micro-turbulent velocities in our models, the blue peak in the line would be smoothed out and shown as a blue asymmetry instead. In addition, an increased Stark broadening would also help remove the discrepancy significantly (Zhu et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The importance of non-equilibrium (NEQ) ionisation and recombination in determining the atomic level populations (and therefore the radiative response to the disturbance) will likely vary from species to species, and the charge states of those species. However, when modelling the radiative response of the atmosphere to flares it is often the case that the statistical equilibrium (SE) solution is sought, given the computational demands of performing time dependent simulations that include physical processes, such as partial frequency redistribution, that are required for certain transitions (recent examples include Rubio da Costa & Kleint 2017;Zhu et al 2019;. This is partly mitigated by using the non-equilibrium electron density from dynamic simulations.…”
Section: Introductionmentioning
confidence: 99%